Review of "retro furniture" interior trend - Atmadi, Tunjung (Eximia, 2022)
This research highlights the retro or repetition, which is a variety of definitions both as part of the past as well as as a creative turmoil that re-application in this post-modernity era. With a comparative descriptive method, the goal to be achieved in this study is to examine retro-style furniture.. It is a form of appreciation to the designers as a form of appreciation in the work of retro-styled furniture that has been born in the era. Where retro is a concept that has ever been popular in the past especially that developed between the years 1930 to around 1970. The characteristic of retro-styled interior design is its attractive nature. The expected outcome of this research study is beneficial to the world of education and society generally in understanding retro furniture. Retro Furniture that has been understood as a concept of antiquity. But in fact, retro-style furniture is not only to be nostalgic but can restore a work that is alive, soulful and high-value.